STRUCTURAL CODE-SWITCHING PATTERNS AS DETERMINED BY TOPIC IN HAUSA - Jibir-Daura, Ramlatu (Sokoto Educational Review, 2018)
The research is a structural approach to the study of code-switching patterns among Hausa- English bilinguals. It is to discover the linguistic structural code-switching patterns as determined by topic in the speeches of Hausa-English bilinguals and their educational implications at the primary and Junior secondary school levels. Un-guarded data vraj collected with audio and video recordings. The population sample is three hundred and eighty-five respondents from Jigawa, Kano, Kaduna, Katsina and Sokoto states. These are states with high concentration of Hausa speakers. The research is a survey which uses interviews, obsen’ations and recordings. The data collected was analysed along structural patterns. The topics were technical/scientific, politics, education, administration, family, childhood experiences transactions and sermons. The structural code-switching patterns discovered were tag, intra and inter-sentential. Tag switches ranked highest and inter-sentential the least in frequency of occurrences. Code-switchings occurred in all the topics but were more with scientific and technical topics but are less in transactions. The findings indicated that topic is a determinant of code-switchings among Hausa-English bilinguals.